2008
DOI: 10.1021/cm802132t
|View full text |Cite
|
Sign up to set email alerts
|

Textural, Structural, and CO2 Chemisorption Effects Produced on the Lithium Orthosilicate by Its Doping with Sodium (Li4−xNaxSiO4)

Abstract: Solid solutions of lithium and sodium orthosilicate (Li 4-x Na x SiO 4 ) were synthesized by coprecipitation. Samples were characterized by powder X-ray diffraction, scanning electron microscopy, N 2 adsorption, and thermogravimetric analyses (dynamic and isothermically). Results showed that the solubility limit of sodium into Li 4 SiO 4 is 0.1, Li 3.9 Na 0.1 SiO 4 . Sodium additions, higher than 0.1, produced the formation of secondary phases. Thermal analyses into a CO 2 flux showed that Li 4-x Na x SiO 4 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
147
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 139 publications
(173 citation statements)
references
References 21 publications
22
147
1
Order By: Relevance
“…Especially Li-1000RHA even obtained with 33.6 wt % maximum absorption, which corresponded to 91.6% efficiency. This higher capacity of Li 4 SiO 4 sorbents were also observed using sodium orthosilicates [12] and RHA-Li 4 SiO 4 sorbent [8].…”
Section: N 2 Absorption Characterizationsupporting
confidence: 69%
“…Especially Li-1000RHA even obtained with 33.6 wt % maximum absorption, which corresponded to 91.6% efficiency. This higher capacity of Li 4 SiO 4 sorbents were also observed using sodium orthosilicates [12] and RHA-Li 4 SiO 4 sorbent [8].…”
Section: N 2 Absorption Characterizationsupporting
confidence: 69%
“…Powders were mixed and then thermally treated at 800 °C for 8 h. A lithium excess of 15 wt% was used to prevent lithium sublimation. 22,32,34 Aft er the Li 8 SiO 6 synthesis, the powder was mechanically mixed with 10 wt% of sodium carbonate (Na 2 CO 3 , Aldrich), or potassium carbonate (K 2 CO 3 , Aldrich), or a 50:50 wt% mixture of both carbonates (20 wt% in total). Th e samples were labeled as follow: Th e Na 2 CO 3 -Li 8 SiO 6 sample was labeled as Na-Li 8 SiO 6 , the K 2 CO 3 -Li 8 SiO 6 sample was labeled as K-Li 8 SiO 6 and the K 2 CO 3 -Na 2 CO 3 -Li 8 SiO 6 sample was labeled as K-Na-Li 8 SiO 6 .…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have indicated that alkaline solid mixtures such as lithium-sodium zirconate, lithium-potassium zirconate and Li-Na ortho-silicate present better CO 2 sorption than pure lithium or sodium zirconate [27]. The latter work showed that the solubility limit of sodium into Li 4 SiO 4 is 0.025% (Li 3.9 Na 0.1 SiO 4 ) and that addition of Na larger than 0.025% produces secondary silicate phase [27].…”
Section: Introductionmentioning
confidence: 97%